3D printing optimization through projection-assisted parameter search (PAPS) - Quiazon, Nina Kamilla J.; Samonte, Sarah N.; Bongolan, Vena Pearl A.; Tapang, Giovanni A. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
3D printing is one of the emerging technologies in science. In the local scene, 3D printers are used by the National Institute of Physics to create miniature models of figures to teach public elementary school students, realizing that visual and hands-on learning is a key tool in teaching Science in early stages of childhood. Since this technology is new in the country, cutting monetary costs is a necessity for average-earning people and government institutions to be able to afford using it. A better value then would mean usability of the technology by the general public, and for the purposes of this research, in the education sector. Minimizing the printing cost would mean cheaper costs not only in monetary value, but also costs in terms of time, effort, and energy. This study aims to find the best orientation (x-y-z axis parameters) of an STL model that gives the latest 3D printing time and least use of filament materials through the rotation of the model in 3D space in order to minimize cost.
Thesis (B.S. Computer Science)--University of the Philippines Diliman
Keywords: Three-dimensional printing; Mathematical optimization